Kewaspadaan terhadap Keluarga dan Harta dalam QS. Al-Taghabun [54]: 14-15 - M. Marovida Aziz (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This article examines and analyzes the attitude that must be taken when family and property become enemies, obstacles and trials. To understand it, that family and property are inseparable, humans are born to have a family, while to meet the daily needs of a family requires property as a basic need such as clothing and food. This paper will explain that in having a family and managing wealth there are more or less trials and tests in it, so in the sura QS. al-Taghabun [64]: 14-15 explains vigilance towards family and property. By using the Ma'nā-cum-Maghzā approach formulated by Sahiron Syamsuddin, the author wants to see the meaning of the main message behind being vigilance of our family and property, by analyzing the language of the verse and looking at the historical context of the verse. With this step, it leads to a concrete conclusion that when dealing with wives and children who hinder us, we should not use violence, and when we get sustenance in the form of wealth we must be able to manage it well and in the right way.